Analisis Pengaruh Gaya Kepemimpinan Partisipatif terhadap Budaya Organisasi dan Produktivitas Kerja Pegawai pada Balai Pelaksana Penyedia Perumahan (P2P) Sulawesi II - Farid Wajdy; Amiruddin Tawe; Uhud Darmawan Natsir (PT Maju Malaqbi Makkarana, 2023)
Participatory leadership or democratic leadership style is the behavior of a leader in making decisions together with his subordinates. Participatory leadership style is closely related to government institutions where bureaucratic reform must be carried out with constitutional principles and democratic principles and promote mutual cooperation to run the organization, while organizational culture is the core value of the process of individual orientation towards a system that is within an organization, as for productivity work is the attitude and behavior of the organization's workforce towards the rules and standards set by the organization, then manifested as behavior and actions within the organization. In the initial observations made within the Balai P2P Sulawesi II to 8 divisional representatives using the LASI (Leadership Adaptibility and Style Inventory) method developed by Paul Hersey and Kenneth Blanchard regarding leader adjustment and style inventory, to determine leadership style with the result stating that style instructional leadership, namely 25% and the smallest value, namely the delegation leadership style, as much as 8%, is more dominant using a participatory leadership style, which is around 67%. The results of preliminary observations show that in carrying out leadership the Head of Balai P2P Sulawesi II is more dominant in using a participatory leadership style. The results of P Values show the number 0.000 or <0.05. This proves that participatory leadership style has a significant effect on organizational culture at Balai P2P Sulawesi II and P Values show the number 0.003 or <0.05. This proves that participatory leadership style has a significant effect on employee work productivity at Balai P2P Sulawesi II